Effect of Mother and Infant Skin to Skin Contact on Early Initiation Breastfeeding: A Meta Analysis - Pertiwi, Mumpuni Intan; Murti, Bhisma; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2022)
Background: Skin to Skin Contact (SSC) of mothers and babies immediately after giving birth provides many benefits at the beginning of breastfeeding, an effective intervention can increase the competence of breastfeeding babies compared to just getting routine care. This study aims to analyze the primary study of the effect of mother-infant skin to skin contact on the success of the first breastfeeding with a meta-analysis. Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: mothers and newborns. Intervention: skin to skin contact. Comparison: Routine care. Outcome: Successful first breastfeeding. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, Science Direct and Springerlink. Keywords to search for articles (“skin to skin contact” OR “early initiation breastfeeding” OR “kangaroo mother care” AND “first breastfeeding” OR “duration breastfeeding” AND “Randomized Control Trials” OR “RCT”). The articles included are full text in English and Indonesian with a Randomized Controlled Trial study design from 2011 to 2021 and reports on the Mean and SD in a multivariate analysis. Article selection is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 aplikasi application. Results: A total of 10 randomized controlled trials from Iran, India, Pakistan, Egypt, and Thailand were selected for a systematic review and meta-analysis. The data collected showed that skin to skin contact increased the success of the first breastfeeding by 1.05 times compared to conventional method care (SMD= 1.10; 95% CI= 0.63 to 1.58; p<0.001). Conclusion: Skin to skin contact can increase the success of the first breastfeeding. Keywords: skin to skin contact, breastfeeding success, meta-analysis. Correspondence: Alfi Makrifatul Azizah. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: alfimakrifatulazizahh@gmail.com. Mobile: +6285375335480.